Decomposition of the central structure of NGC 2273 in the NIR: a case study - Schey, Leonid; Heidt, Jochen; Pramskiy, Alexander; Thompson, D.; Agapito, G.; Esposito, S.; Gredel, Roland; Miller, D.; Pinna, E.; Puglisi, A.; Rossi, F.; Seifert, Walter; et al. (Astronomische Nachrichten, 2023)
The Seyfert 2 galaxy NGC 2273 is a prime target to explore how active nuclei can be fed. It has a star-forming innermost nuclear ring with a radius of 0.33kpc from where material may be funneled to the supermassive black hole in its center. In this article, we discuss high-resolution adaptive optics aided JHKs images of NGC 2273 taken with the Large Binocular Telescope. Using Galfit we decomposed the innermost part of NGC 2273 into a core, a disk, and a ring using 58 parameters, 44 of them were used to describe the ring. The stellar mass of the ring was found to be 12 ×108M⊙\ × 10^8\mathrmM_ødot \, a factor of 10 higher than its molecular gas mass. A continuous gas flow via the main stellar bar of NGC 2273 during the lifetime of the bar of up to 10 M⊙yr−1\ \mathrmM_ødot \mathrmyr^-1 \ is required to provide the fuel for the formation of the stars unless the star formation efficiency is on the order of 10%. This does not affect the fueling of the nuclear source as the amount of molecular gas required for this low-luminosity active galaxy to achieve this is on the order of 104M⊙\ 10^4\mathrmM_ødot \ only.